Generation of Dual-Frequency Microwave Pulse Based on Active Mode-Locked Optoelectronic Oscillator - Junfeng Ren; Ping Li; Chenyang Ma; Cheng Gu; Boxiong Cui; Huitong Yang; Zhengyang Xie; Xin Zhao; Zheng Zheng (IEEE Photonics Journal, 2025)
Active mode-locked optoelectronic oscillator(AML-OEO) is a high-quality pulsed microwave source that can be used to generate microwave pulse signals in various forms. We introduce a structure for an AML-OEO, which is intended to generate dual- frequency microwave pulses. In the context of a dual-band microwave pulse sequence, each sub-pulse incorporates signals having a pair of distinct center frequencies. Different filters can be selected for adjustment according to the band requirements of different scenarios. The generated dual-band microwave pulse signals exhibit excellent phase noise performance at both carrier frequencies, we can generate pulse signals with phase noise as low as −120.9 dBc/Hz@10 kHz at 6.55 GHz and −120.5 dBc/Hz@10 kHz at 10.79 GHz. This structure is simpler and more compact, and is expected to play a role in multi-band radar, communications and other fields in the future.